2022
DOI: 10.1259/dmfr.20210365
|View full text |Cite
|
Sign up to set email alerts
|

Is jaw fractal dimension a reliable biomarker for osteoporosis screening? A systematic review and meta-analysis of diagnostic test accuracy studies

Abstract: Objectives: To summarize the evidence on the feasibility of maxillomandibular imaging exams-related fractal dimension (FD) in screening patients with osteoporosis. Methods: This registered systematic review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses of Diagnostic Test Accuracy statement. High sensitivity search strategies were developed for six primary databases and grey literature. Quality Assessment of Diagnostic Accuracy Studies (QUADAS-2) items evaluated the risk of bia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 22 publications
2
12
0
2
Order By: Relevance
“…There are studies showing that FD values can be used to predict the presence of osteoporosis and that there is a significant correlation between them. 37,[45][46][47][48] In our study, we found FD values lower in RTx patients than in the healthy group. When the immunosuppressive agents used by the patients are evaluated, this situation can be clarified by the disorder in bone-mineral balance caused by these drugs.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…There are studies showing that FD values can be used to predict the presence of osteoporosis and that there is a significant correlation between them. 37,[45][46][47][48] In our study, we found FD values lower in RTx patients than in the healthy group. When the immunosuppressive agents used by the patients are evaluated, this situation can be clarified by the disorder in bone-mineral balance caused by these drugs.…”
Section: Discussionsupporting
confidence: 56%
“…As the duration of disease increased in RTx patients, the rate of osteoporosis increased. 37,39 This difference can be explained by the fact that the patients in our study had a longer disease state in terms of total duration. In a study conducted in 2016; FD values were found to be lower than the healthy control group in the evaluation performed with panoramic radiography in patients diagnosed with CKD.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…We used FD in this research considering the measure's low execution complexity and the use of free software. We chose DPR for examination since it has been widely used in studies 29 and presents low execution complexity, high availability, and low cost, being a viable alternative for implementation in health services.…”
Section: Discussionmentioning
confidence: 99%
“…Differences related to ROIs are important in using FA. The selection area and size of these regions are greatly diverse since variations mainly consider mandible regions and shapes are mostly square or rectangular, with different sizes [29][30][31] .…”
Section: Discussionmentioning
confidence: 99%